Endovascular treatment of symptomatic severe intracranial atherosclerotic stenosis with a novel intracranial dedicated drug-eluting stent: a more effective treatment approach - Ma, Lin; Wang, Fei; Feng, Hao; Yan, Shuo; Xu, Ji-Chong; Cheng, Ying-Sheng; Fang, Chun (Frontiers in Neurology, 2024)
Endovascular treatment of severe intracranial atherosclerotic stenosis (ICAS) using coronary drug-eluting stents (DESs) significantly reduces the risk of in-stent restenosis (ISR) and stroke recurrence. However, there are few reports regarding the treatment of ICAS with intracranial dedicated DES. Herein, we present our experience with the feasibility, safety, and medium-term follow-up outcomes of a novel intracranial DES, named NOVA stent, in patients with symptomatic severe ICAS (  70%).From December 2021 to May 2022, patients with symptomatic severe ICAS who underwent implantation of the NOVA stent in our institution were retrospectively analyzed for procedural results, perioperative complications, imaging and clinical follow-up outcomes.Twenty-four patients, 16 (66.7%) with anterior circulation lesions and 8 (33.3%) with posterior circulation lesions, were enrolled. All patients with intracranial ICA (n = 6), middle cerebral artery (n = 10), basilar artery (n = 3), intracranial vertebral artery (n = 3), and the vertebrobasilar junction (n = 2) stenosis were treated successfully using NOVA stents. The severity of stenosis ranged from 75 to 96% (mean 85.9%) before treatment and this was reduced to 0 to 20% (mean 8.6%) immediately after stent placement. Symptomatic distal embolism occurred in one case; however, there were no other perioperative complications. The mean follow-up duration was 12.2 ± 1.06 months. No symptomatic ischemic events occurred during follow-up. Follow-up cerebral angiography was performed in 22 of 24 patients (91.7%), and significant ISR occurred in one patient (4.2%) .Our results demonstrate that implantation of the novel intracranial DES NOVA in severe ICAS is feasible, safe, and effective in selected cases, reducing the incidence of ISR, and showing excellent midterm clinical outcomes, providing a promising option for ICAS treatment.